Can You Sue the Government? An Examination of the Legal Doctrines for Government Liability Regarding Their Involvement with Wind Power Development - Kim, Esther Y. (Columbia Journal of Environmental Law, 2019)
With increasing government involvement in the development of wind power, neighboring landowners experiencing harms related to wind turbines might wish to—indeed, in some cases may need to—recover from the government as well as private parties. They may wish to bring nuisance claims against the government, which will largely mirror claims against private wind developers, and may bring claims alleging a Taking in violation of the Fifth Amendment of the United States Constitution. Government liability for harms caused by wind farms may increase the costs of wind power development. This Note determines that the Takings claim is the stronger claim and proposes which Takings jurisprudence courts should apply, depending on the nature and scope of government action in particular cases. Specifically, this Note focuses on the three possible ways that the government may become involved with the development of wind farms: (1) explicit grants of nuisance immunity to wind farms; (2) government authorization of wind farms; (3) and wind farms planned and developed by the government on government lands (hereafter “government-developed” wind farms).